Odpowiedzi

Najlepsza Odpowiedź!
2010-02-19T12:46:40+01:00
(x+1)²-2x² = x² + 2x + 1 - 2x² = 2x - x² + 1
-2(3x-1)² + 18x² = -2(9x² - 6x + 1) - 18x² = -18x² - 18x² + 12x - 2 = -36x² + 12x - 2
3(2a+1)(2a-1)= 3(4a² - 1) = 12a² - 3
(x+8)(x-8) -(x²+8) = x² - 64 - x² - 8 = -72
-(x-4)² + (x+4)² = -(x² - 8x + 16) + x² + 8x + 16 = -x² + x² +8x +8x -16 + 16 = 16x
(3t-1)² - (3t+1)(3t-1)= 9t² - 6t + 1 -(9t² - 1) = 9t² - 9t² - 6t + 1 +1 = -6t + 2
2010-02-19T12:49:57+01:00
(x+1)²-2x²= x² + 2x + 1 - 2x² = -x² + 2x + 1

-2(3x-1)²+18x²= -2 * (9x² + 1) + 18x² = -18x² - 2 + 18x² = -2

3(2a+1)(2a-1) = 3* (4a² - 2a + 2a - 1) = 12a² - 6a + 6a -3 = 12a² - 3

(x+8)(x-8)-(x²-8)= x² - 8x + 8x - 64 - x² +8 = -56

-(x-4)²+(x+4)²= - (x² -8x + 16) + x² + 8x + 16 = -x² +8x - 16 + x² + 8x + 16 = 16x

(3t-1)²-(3t+1)(3t-1)= 9t² - 6t + 1 - (9t² -3t + 3t -1) = 9t² -6t + 1 - 9t² + 3t - 3t + 1 = 2 -6t

-2(3x-1)²+18x²= -2 * (9x² -6x + 1) + 18x² = -18x² +12x - 2 + 18 x² = -2 +12x

3(2a+1)(2a-1) = 3* (4a² - 2a + 2a - 1) = 12a² -3

(x+8)(x-8)-(x²-8)= x² - 64 -x² + 8 = -56

-(x-4)²+(x+4)²= -(x²-8x+16) + x²+8x+16 = -x²+8x-16 + x²+8x+16 = 16x

(3t-1)²-(3t+1)(3t-1)= 9t² - 6t + 1 - (9t² -1) = - 6t + 2